ISOLATION OF PROTEINS FROM POTATO TUBERS - Murawska, Zofia; Dębski, Janusz; Szajko, Katarzyna; Lebecka, Renata (Plant Breeding and Seed Science, 2017)
Here we optimized an efficient and reproducible method for proteins isolation from potato tubers for quan-titative proteomic analysis, aimed at detection of differentially expressed proteins upon various experimental conditions.